2020
DOI: 10.3390/nano10050915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humidity on Light-Activated NO and NO2 Gas Sensing by Hybrid Materials

Abstract: Air humidity is one of the main factors affecting the characteristics of semiconductor gas sensors, especially at low measurement temperatures. In this work we analyzed the influence of relative humidity on sensor properties of the hybrid materials based on the nanocrystalline SnO2 and In2O3 and Ru (II) heterocyclic complex and verified the possibility of using such materials for NO (0.25–4.0 ppm) and NO2 (0.05–1.0 ppm) detection in high humidity conditions (relative humidity (RH) = 20%, 40%, 65%, 90%) at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In the first mechanism () proposed by Heinrich and Cox, water vapor displaces adsorbed oxygen, forming hydroxyls (OH ′ ) and releasing a vacancy (V O •• ) and e ′ . This mechanism seems to be supported by a strong reduction of the O 2 ′ /OH • radicals’ ratio in humid conditions, as recorded by EPR measurements for crystalline SnO 2 . In the second mechanism, proposed by Heiland and Kohl (6,7), either rooted (OH) O • or two terminal (OH ′ ) groups and an oxygen vacancy are formed.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the first mechanism () proposed by Heinrich and Cox, water vapor displaces adsorbed oxygen, forming hydroxyls (OH ′ ) and releasing a vacancy (V O •• ) and e ′ . This mechanism seems to be supported by a strong reduction of the O 2 ′ /OH • radicals’ ratio in humid conditions, as recorded by EPR measurements for crystalline SnO 2 . In the second mechanism, proposed by Heiland and Kohl (6,7), either rooted (OH) O • or two terminal (OH ′ ) groups and an oxygen vacancy are formed.…”
Section: Discussionmentioning
confidence: 59%
“…This mechanism seems to be supported by a strong reduction of the O 2 ′/OH • radicals' ratio in humid conditions, as recorded by EPR measurements for crystalline SnO 2 . 62 In the second mechanism, proposed by Heiland and Kohl 63 (6,7), either rooted (OH) O…”
Section: ••mentioning
confidence: 99%
“…Furthermore, electron paramagnetic resonance (EPR) spectroscopy measurements carried out by Nasriddinov et al on the surface of SNO 2 and SNO 2 /Ru confirmed that O 2 − species can be easily replaced by OH* radicals in a humid atmosphere [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…(a) Responses of SnO 2 decorated with different noble metals under UV-illumination [29] ; (b-d) ZnO with different nanostructures and (e) their gas-sensing responses [27] ; (f) TEM image showing Aunanoparticle decorated ZnO and (g) gas sensing properties of pure ZnO (red line) and Aunanoparticle decorated ZnO (black line) [28] ; (h) Response curve of hollow TiO 2 microspheres [59] ; (i) Sensing behaviors of NiO under illumination of lights with different wavelengths at room temperature [30] 表 2 带隙宽度>3.1 eV 的光激发气敏材料 NiO 372 ppb NO 2 可见光 -溶剂热 88.94% [30] ZnO 100 ppm 甲醛 365 nm -溶剂热 12.61 [27] ZnO 50 ppm NO 2 365 nm -溶剂热 15 [35] ZnO 纳米线 100 ppm 甲醛 365 nm -溶剂热 12.61 [36] ZnO 纳米棒 30 ppb 臭氧 370 nm -溶剂热 44% [37] ZnO/Au NP 6 ppm NO x 白光 100 mW/cm 2 溶剂热 78% [38] Au-ZnO 500 ppm 乙醇 白光 6 mW/cm 2 热蒸发 62 [28] ZnO/纳米 Ag 颗粒 5 ppm NO 2 470 nm 75 mW/cm 2 溶剂热 1.545 [39] TiO 2 纳米球 5 ppm 甲醛 365 nm -溶剂热 - [59] NiO@TiO 2 50 ppm 乙醚 365 nm 36 W/m 2 球磨 31.02 [31] C 量子点/NiO 30 ppm CH 4 UV -溶剂热 - 能 [40] . Ru 修饰 In 2 O 3 对(c)NO 和(d)NO 2 的气敏响应性能 [41] . Pd 修饰 WO 3 的(e)形貌及(f)对 H 2 的气敏性能 [42] .…”
mentioning
confidence: 99%
“…Response of In 2 O 3 , In 2 O 3 +RuITP samples to (c) NO and (d) NO 2 in dry and humid air at room temperature [41] . (e) SEM image and (f) gas sensing properties of PdO-decorated WO 3 to H 2 [42] ;…”
mentioning
confidence: 99%